2013
DOI: 10.1097/iae.0b013e3182877585
|View full text |Cite
|
Sign up to set email alerts
|

Povidone–iodine Contact Time and Lid Speculum Use During Intravitreal Injection

Abstract: The use of 5% PI causes a significant reduction in bacterial colonies, and 30 seconds of exposure appears to be an adequate time to decrease conjunctival bacterial counts. Lid speculum use before intravitreal injection does not affect the overall conjunctival flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 48 publications
1
39
1
4
Order By: Relevance
“…A recent prospective, randomized study investigating the contact time (15, 30, 60 s) of 5% PI during 131 IVI showed that a 30-s PI exposure reduced the resident bacterial load significantly compared to 15 s only [88]. This is also confirmed in a laboratory study investigating the bactericidal activity of PI dilute preparations [82].…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapysupporting
confidence: 65%
“…A recent prospective, randomized study investigating the contact time (15, 30, 60 s) of 5% PI during 131 IVI showed that a 30-s PI exposure reduced the resident bacterial load significantly compared to 15 s only [88]. This is also confirmed in a laboratory study investigating the bactericidal activity of PI dilute preparations [82].…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapysupporting
confidence: 65%
“…Friedman et al [114] found a significant reduction in conjunctival bacterial growth after a 30 s exposure to 5% PI, and a further reduction with a 60+ second exposure, while 15 s was inadequate.…”
Section: Reviewmentioning
confidence: 99%
“…There is some concern that the speculum can induce lid squeezing and thus the secretion of infectious organisms from the lid margin. However, Friedman et al found no change in conjunctival cultures after placement of a lid speculum [ 24 ]. While other techniques, such as bimanual retraction, have proven suffi cient, the lid speculum is still common practice for intravitreal injections.…”
Section: Eyelid Speculummentioning
confidence: 98%